D-erythrose supports nitrogenase activity in isolated Anabaena sp. strain 7120 heterocysts. - Privalle, L S (1984)
Among organic compounds tested for their ability to support nitrogenase activity in isolated heterocysts of Anabaena sp. strain 7120 under argon, D-erythrose (5 mM) was unique in supporting acetylene reduction at 10 times the control rates. Higher concentrations of D-erythrose exhibited substrate inhibition. At 50 kPa of H2, all concentrations of D-erythrose inhibited H2-supported acetylene reduction. The effects of D-erythrose on nitrogenase activity were explored. Erythrose enhanced 15N2 incorporation by heterocysts, but NADP+ did not enhance erythrose-supported acetylene reduction. H2 protected nitrogenase from O2 inactivation, but erythrose did not; erythrose did not counter protection by H2. Tests with inhibitors of electron transport showed that erythrose-supported acetylene reduction requires electron flow through ferredoxin, a b-type cytochrome, and a 2,5-dibromo-3-methyl-6-isopropyl-p-benzoquinone-sensitive transfer agent whose electron flow is not mediated through the plastoquinone and Rieske iron protein.